Neutrophil-to-lymphocyte ratio as a predictor of survival in laryngeal carcinoma - Barreto, Joana (2024)
Introduction: The neutrophil-to-lymphocyte ratio (NLR) is an inflammatory marker and is associated with a worse prognosis in various neoplasms. Recently, it has also been associated with a worse prognosis in laryngeal carcinoma. Aim: To assess the association between NLR and survival in patients with laryngeal carcinoma at our institution. Material and Methods: This retrospective study included 118 patients with laryngeal carcinoma treated at our institution. Pre-treatment NLR was assessed, as well as demographic characteristics and the American Joint Committee on Cancer (AJCC) prognostic stage. Patients with acute infections at the time of the analytical study were excluded. Cox regression was used for each of the variables alone to study their association with survival. The variables with a statistically significant result (p<0.05) were then included in a multivariate analysis to exclude potential confounding factors. Results: A statistically significant association was found between NLR and survival, regardless of prognostic stage, with an adjusted Hazard Ratio of 1.22 (p<0.001). Conclusion: NLR is an independent prognostic factor for survival in patients with laryngeal carcinoma. NLR can serve as a cost-effective prognostic biomarker.